Propriedades eletrônicas e de transporte de nanoestruturas de carbono - Girão, Eduardo Costa (2011)
As the miniaturization limit of the physical size of Si-based electronics is projected to be reached in a near future, solid-state alternatives must be investigated in the pursuit of further scaling down the effective operational device structures, while considering growingly important problems such as heat dissipation and noise associated with reduced dimensionality. In this quest, it is clear that semiconducting carbon nanosystems are solid front-runner candidates to compose the building blocks for devices at molecular and atomic scales. Graphene and carbon nanotubes are the most studied members of this class of structures which extends over a broad collection of systems. These carbon nanostructures present a wealth of promising physical and chemical properties which is reflected in the number of scientific works having these systems as focus [1]. Even though the science of carbon nanostructures has a long path ahead before reaching the shelves of stores after being transformed into technology, the scientific community has been walking fast towards the understanding and the control of such systems in order to shorten this gap. In this thesis we theoretically studied the electronic structure and transport properties of a number of carbon nanostructures, such as toroidal carbon nanosystems and complex assembled graphitic nanoribbons. Our electronic structure calculations are based on a tight-binding model including a Hubbard Hamiltonian to describe the influence of spin on the electronic states. The electronic transport properties were computed using the Landauer formalism and a Green’s function approach to determine the quantum transmission in nanoscaled systems. Part of these calculations were performed with computational packages developed specifically for this thesis. In particular, we developed an extension of an efficient algorithm to calculate the Green’s function on a parallel computational infrastructure. Carbon nanotori display specific electronic structure compared to carbon nanotubes, since this geometry imposes a supplemental degree of spatial confinement. As a consequence, additional conditions on the structure geometry have to be obeyed for a given torus to be metallic. Here we analyzed carbon nanotori from two different perspectives: two-terminal systems with a variable angle between the terminals and multi-terminal structures. These rings are potential systems for nanoelectronic application as their particular geometry allows the current to flow through the system along different electronic paths. This results in interesting transport properties dictated by electron interference effects which vary with the angle between the electrodes and the atomic details of the nanotorus-electrode junction. We showed that the presence of multi-terminals adds new features to the electronic transport on these tori as the number of possibilities for the electronic flow increases quickly with the number of electrodes. It turns out that the conductance is characterized by a set of resonant peaks which are related to specific electronic paths. These results are rationalized into a set of rules to determine the path for the electrical current as a function of the impinging electron energy. In the second part of the thesis we studied the physical properties of a class of complex graphitic nanoribbons that we called wiggles. The atomic structure of these wiggles can be described by a reduced set of factors since they can be built using straight carbon nanoribons as basic building blocks. We show that carbon nanowiggles present a broader set of electronic and magnetic properties in comparison to those of their constituents (graphene nanoribbons). This is mainly due to the formation of edge domains resulting from the successive repetition of parallel and oblique graphene nanoribbon sectors along the wiggle’s periodic direction. We demonstrate that carbon wiggles present multiple magnetic states which can be exploited to tune the physical properties of these systems. These different magnetic states lead to dissimilar electronic structure and transport properties for the wiggles so that the electronic current on these systems can be tuned by selecting specific values for the impinging electron energy as well as its spin and the wiggle’s magnetic state. These properties make carbon nanowiggles potential candidates as new nanodevices. Finally, we expect that the work reported in this thesis will constitute an important contribution to the investigation of the physical properties of carbon nanostructures. We show that carbon nanotori and nanowiggles present a series of new properties that can enable their use in nanoelectronics. As experimental studies on carbon nanomaterials have been developed at a fast pace, we project the findings presented in this thesis to be a great opportunity to confront theory and experiment in the proposal of new nanoscaled devices with specific electronic and transport properties.